2013
DOI: 10.1088/0957-4484/24/20/202001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of antimonide nanowires

Abstract: Antimonide semiconductors are suitable for low-power electronics and long-wavelength optoelectronic applications. In recent years research on antimonide nanowires has become a rapidly growing field, and nano-materials have promising applications in fundamental physics research, for tunnel field-effect transistors, and long-wavelength detectors. In this review, we give an overview of the field of antimonide nanowires, beginning with a description of the synthesis of these nano-materials. Here we summarize numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 130 publications
4
84
0
Order By: Relevance
“…In the latter case, no field effect has been reported so far. Meanwhile, GaSb p-type nanowires are also the subject of intense research, much for the same reasons [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, no field effect has been reported so far. Meanwhile, GaSb p-type nanowires are also the subject of intense research, much for the same reasons [9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the incongruent evaporation of III and V elements when InSb was heated [9], the V/III ratio cannot be directly and independently controlled. The V/III precursor ratio supply was unbalanced during the growth [12][13], which is bad to the growth of InSb nanowires by direct evaporation of InSb.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, some novel structures like zinc blend or wurtzite or zinc blend twinning superlattice have been investigated [ 82 , 154 156 ]. However, antimonide NWs with the ZB structure are dominating from the previous reports, and this keeps true even for ternary antimonide NWs with only a small Sb concentration [ 157 ]. Although Mandl et al [ 24 ] and Pozuelo et al [ 76 ] have reported WZ structure of antimonide NWs.…”
Section: Reviewmentioning
confidence: 90%